Gift Giving Kalipay sa Pag-Ambitanay (Sukacita Dalam Berbagi) Masyarakat IP’s Di Dueñas, Iloilo, Philippines - Sherlin Norma Azzahra; Endang Sri Maruti; Sri Lestari (AMMA : Jurnal Pengabdian Masyarakat, 2024)
On this humanitarian project the CDC community with me as an exchange student at iloilo science and technology university did the social activities done in barangay taminla, duenas, iloilo. This activity is done to bring good and positive results to the indigeneous/indigenous peoples who have long lived in the area. It is also done as one of the momentum in celebrating the joy of Christmas in 2023. People in this area need some attention because they are less fortunate to experience facilities, education systems as well as tools and infrastructure. In addition, I have adopted the practice of the two pancasila practice of a just and sensible humanity that is expected to have an effect on those who do need help. Based on humanity we Shared and rejoiced together in taminla, Philippines.